Mobile Learning Based on a Multisensory Approach to Improve Descriptive Text Reading Skills of Deaf Students - Konradus Silvester Jenahut; G.A.P. Suprianti; Endang Nurhayati; Margana; Bilqis Salsabila S. Safa; Lamri (LPPM Undiksha, 2025)
The limitations of deaf students in hearing significantly impact the minimal reception of information from their environment. This encourages deaf students to utilize their visual senses more by reading. This study aims to create a mobile learning product based on a multisensory approach to learning to read descriptive texts to improve the descriptive text reading skills of deaf students. This study uses a research and development method by adopting the Four-D model as a procedure for developing the product. The subjects in this study were deaf students, 2 media experts, 2 material and language experts, and an Indonesian subject teacher. This study's data were from observations, interviews, and questionnaires. The data analysis technique used a qualitative descriptive approach and a quantitative descriptive approach. This study has produced mobile learning based on a multisensory approach to learning to read descriptive texts that is feasible and practical for deaf students. In addition, this mobile learning is equipped with visual, tactile, and interactivity elements that support the multisensory principle that can be implemented in learning to read descriptive texts. This study concludes that mobile learning is very effective in helping deaf students understand the material and overcome the limitations of learning resources. This research implies that mobile learning can help overcome the limitations of learning resources for deaf students and is very effective in supporting the improvement of reading skills.